Taking the Long Way Home: U.S. Tax Evasion and Offshore Investments in U.S. Equity and Debt Markets - HANLON, MICHELLE; MAYDEW, EDWARD L.; THORNOCK, JACOB R. (Journal of Finance, 2015)
ABSTRACT We empirically investigate one form of illegal investor‐level tax evasion and its effect on foreign portfolio investment. In particular, we examine a form of round‐tripping tax evasion in which U.S. individuals hide funds in entities located in offshore tax havens and then invest those funds in U.S. securities markets. Employing Becker's ( ) economic theory of crime, we identify the tax evasion component by examining how foreign portfolio investment varies with changes in the incentives to evade and the risks of detection. To our knowledge, this is the first empirical evidence of investor‐level tax evasion affecting cross‐border equity and debt investment.